Computer organisation and architecture : evolutionary concepts, principles, and designs - Chakraborty, Pranabananda (Boca Raton, FL : CRC Press, 2021)
Computer organization and architecture is becoming an increasingly important core subject in the areas of computer science and its applications, and information technology constantly steers the relentless revolution going on in this discipline. This textbook demystifies the state of the art using a simple and step-by-step development from traditional fundamentals to the most advanced concepts entwined with this subject, maintaining a reasonable balance among various theoretical principles, numerous design approaches, and their actual practical implementations. Being driven by the diversified knowledge gained directly from working in the constantly changing environment of the information technology (IT) industry, the author sets the stage by describing the modern issues in different areas of this subject. He then continues to effectively provide a comprehensive source of material with exciting new developments using a wealth of concrete examples related to recent regulatory changes in the modern design and architecture of different categories of computer systems associated with real-life instances as case studies, ranging from micro to mini, supermini, mainframes, cluster architectures, massively parallel processing (MPP) systems, and even supercomputers with commodity processors. Many of the topics that are briefly discussed in this book to conserve space for new materials are elaborately described from the design perspective to their ultimate practical implementations with representative schematic diagrams available on the book's website. Key Features Microprocessor evolutions and their chronological improvements with illustrations taken from Intel, Motorola, and other leading families Multicore concept and subsequent multicore processors, a new standard in processor design Cluster architecture, a vibrant organizational and architectural development in building up massively distributed/parallel systems InfiniBand, a high-speed link for use in cluster system architecture providing a single-system image FireWire, a high-speed serial bus used for both isochronous real-time data transfer and asynchronous applications, especially needed in multimedia and mobile phones Evolution of embedded systems and their specific characteristics Real-time systems and their major design issues in brief Improved main memory technologies with their recent releases of DDR2, DDR3, Rambus DRAM, and Cache DRAM, widely used in all types of modern systems, including large clusters and high-end servers DVD optical disks and flash drives (pen drives) RAID, a common approach to configuring multiple-disk arrangements used in large server-based systems A good number of problems along with their solutions on different topics after their delivery Exhaustive material with respective figures related to the entire text to illustrate many of the computer design, organization, and architecture issues with examples are available online at http://crcpress.com/9780367255732 This book serves as a textbook for graduate-level courses for computer science engineering, information technology, electrical engineering, electronics engineering, computer science, BCA, MCA, and other similar courses.
Preface. Acknowledgements. Author. Part I Fundamental Computer Organisation. 1 Computer and Its Environment. 2 Computer System Organisation. 3 Processor Basics - Structure and Function. 4 Memory Organisation. 5 Input-Output Organisation. 6 Control Unit: Design and Operation. 7 Arithmetic and Logic Unit Organisation. Part II High-End Processor Organisation. 8 Pipeline Architecture. 9 RISC Architecture. 10 Parallel Architectures. Additional Reading. Suggested Websites. Index.
OCLC-licensed vendor bibliographic record.
Keywords: Computer organization; Computer architecture; COMPUTERS / Computer Engineering; COMPUTERS / Computer Science; COMPUTERS / General